Tinjauan Yuridis dan Dinamika Pengaturan Koperasi Jasa Keuangan Syariah: Kajian Isu Terkini Perkembangan Syariah Indonesia - Arrizal, Arrizal (Jurnal El-Thawalib, 2025)
The rapid growth of Islamic cooperatives in Indonesia requires regulations that are adaptive to technological advances, while still upholding the principles of maqashid sharia. This study aims to evaluate the strengths and weaknesses of the regulatory framework of Islamic financial services cooperatives in Indonesia and formulate recommendations for substantive strengthening in accordance with maqasid sharia. The method used is qualitative with a literature study approach, with primary data including Law No. 25 of 1992, Government Regulation No. 9 of 1995, and several other regulations, while secondary data include books and journal articles related to Islamic economics and cooperatives. The data collection technique is done through document review and literature study, then the data is synthesized descriptively. The results show that the current regulation still focuses on formal aspects, there is no regulation on the range of profit-sharing ratio or murabaha margin limit, the flexibility of deposit contributions has not been accommodated, and the lack of detailed ratio and margin reporting provisions. Operational standards for al-hiwalah, rahn, qard, and wakalah services are not yet uniform. The level of sharia literacy of members is low, the competence of certified human resources is minimal, there is a lack of external sharia audits, and sharia fintech guidelines for cooperatives do not yet exist. It is recommended to set a minimum-maximum ratio range and murabaha margin limit, require progressive contribution schemes and measurable qard tenors, obligation of at least one sharia manager and one certified DPS in each KSPS, implementation of annual external sharia audits, issuance of cooperative sharia fintech guidelines, and addition of new contract flexibility annexes in the PMK. With these steps, it is hoped that maqashid sharia can be internalized in cooperative regulations and practices, strengthening its role in empowering the people’s economy.